Spectral content of Pc5–6/Pi3 geomagnetic pulsations and their efficiency in generation of geomagnetically induced currents - Sakharov Ya.; Yagova Nadezda; Pilipenko Vyacheslav (Russian Journal of Earth Sciences)
ULF geomagnetic pulsations till recent time have been an underestimated factor of space weather hazard to technological systems. The efficiency of GIC generation by geomagnetic pulsations depends on frequency and spatial distribution of the pulsation’s magnetic field. To clarify how the spectral content of Pc5–6/Pi3 (periods 3–15 min) geomagnetic pulsations influences their efficiency in GIC generation, the inter-relations between amplitudes of GIC and magnetic field variations are studied statistically. For that, we use the data of four-year (2014–2018) continuous GIC recording at the Vykhodnoy auroral station and geomagnetic pulsations at the nearest stations of IMAGE magnetometer network. Potentially risky 10 A GICs can originate from non-storm pulsations with amplitudes about few tens of nanotesla which are common at auroral latitudes. On average, multi-harmonic pulsations are more effective in GIC generation that 1-harmonic ones. The pulsations producing essential GICs preferably occur at pre-noon hours under moderate auroral activity.